Utilization of ChatGPT and Artificial Intelligence in Educational Transformation: Trends, Challenges, and Effects on the Learning Process - Bintang Fauzan Rayadika; Wahju Tjahjo Saputro; Dewi Chirzah; Zohaib Hassan Sain; Abdul Said Bin Ambotang (Unversitas Muhammadiyah Mataram, 2026)
This study aims to identify and analyse the relationship between the level of student dependence on Artificial Intelligence (AI) applications, particularly ChatGPT, and its impact on their critical thinking skills, in line with educational transformation issues in the digital era. This quantitative research employed a convenience non-probability sampling approach, involving 112 student respondents in Indonesia. Data were analysed using reliability tests, normality tests, and the Paired Sample T-test. The findings indicate a high level of ChatGPT usage (Mean Score, M = 4.12), confirming students' enthusiasm for utilizing the tool for learning effectiveness and time efficiency. However, the statistical test revealed a significant difference between the level of ChatGPT usage and students' critical thinking ability (Sig. (2-tailed) = 0.009 < 0.05). This difference suggests that excessive reliance on the tool has the potential to impede the development of social and collaboration skills, and may significantly reduce students' learning independence and critical thinking ability. The study concludes that educational institutions must promptly formulate wise policies to guide students in optimally utilizing AI as a learning assistant, not as a substitute for the thinking process to ensure a balanced and sustainable educational transformation.